Influence of the size of gold nanoparticles dispersed in glass matrix on optical properties. Issue 7 (May 2020) - Singla, Shivani; Achanta, Venu Gopal; Pandey, Om Prakash; Sharma, Gopi
Abstract: Glasses containing noble metal nanoparticles (MNPs) are in demand for optical switching devices because of their large third-order nonlinear optical coefficients associated with the localized surface plasmon resonance (LSPR) of metal nanoparticles. While the MNPs can be chosen based on the operation wavelength as the geometry of the MNP governs the LSPR, efforts are on to develop glasses having a uniform distribution of particles in its matrix. In this paper, we report the MNP doped glass preparation and their properties. Bismuth borate glass with a molar composition of 35-Bi2 O3 :65-B2 O3 and also gold nanoparticles (GNPs) of different sizes (10 nm, 40 nm and 100 nm) dispersed in these glasses are prepared using conventional melt quench technique. X-ray diffraction (XRD) is carried out to study the modification in structure with the variation in the size of the GNPs. Morphological studies have been carried out using Field Emission Scanning Electron Microscopy (FESEM) and the variation in the thermal stability of the prepared system has been observed using Differential Thermal Analysis (DTA). Prepared samples are characterized by Uv–Vis spectroscopy, ellipsometry and Z-scan to study the linear and nonlinear optical behaviour of the material. From ellipsometry results, the refractive index in the UV-VIS-NIR region is estimated and it is found to increase with the increase in particle size. The nonlinear optical properties were studied using the Z-scan technique with a Ti: sapphire laser at 800 nm and nonlinear parameters (nonlinear absorption and nonlinear refractive index) is obtained after fitting the experimental data.